Response of parsley to different population densities of Meloidogyne arenaria - Lozada-Villanueva, Leslie Sharon (2021)
The effect of initial population density (Pi) of the peanut root-knot nematode, Melodoigyne arenaria, on curly leaf parsley growth was assessed in this study. The population densities of M. arenaria ranged from 0 to 64 eggs + second-stage juveniles (J2)/cm3 soil in sterile sandbags. The root gall index (RGI), reproduction factor (RF), fresh leaf weight (FLW), dry leaf weight (DLW), root fresh weight (RFW), root length (RL), leaf height (LH), and chlorophyll index (SPAD) were determined at 90 days after inoculation. FLW, DLW, RFW, LH, and SPAD data were fitted to the Seinhorst equation, y = m + (1 - m) zPi-T, to determine the tolerance limit T = 0.25 eggs +J2/cm3 soil for FLW, DLW, RFW, and LH, with relative means (m) of 0.52, 0.24, 0.22, and 0.4 respectively; conversely, the T value for SPAD was 0.125 eggs + J2/cm3 soil and with a m of 0.26. All biometric variables decreased with an increase in the initial population density (Pi). Nevertheless, the highest RF of M. arenaria in parsley was 78.92 for a Pi = 8 eggs + J2/cm3 soil, with an RGI value of 5 from Pi = 1 eggs + J2/cm3. Curly leaf parsley growth decreased with an increase in Pi of M. arenaria.